Pengaruh Modal Kerja Dan Transaksi Online (E-Commerce), Dan Labelisasi Halal Terhadap Pendapatan UMKM Muslim Di Kota Medan Dalam Konsep Mashlahah - Dinda Putri Hafira; Nur Ahmadi Bi Rahmani; Laylan Syafina (Universitas Labuhanbatu, 2023)
This study aims to find out the effect of working capital and online transactions (e-commerce), and halal labeling on the income of Muslim umkm in Medan city in the concept of Mashlahah. This research uses quantitative methods, primary data collection techniques by distributing questionnaires which have a sample of 100 respondents consisting of all Muslim MSMEs in Medan City. This study uses the SPSS statistical tool. Data were analyzed using multiple linear regression analysis method. The results of this study indicate that working capital has a positive and significant effect on income. This is evidenced by the tcount value for the Working Capital variable (2.434) which is greater than ttable (1.984) and the sig value 0.017 <0.05, Online/E-Commerce Transactions have a positive and significant effect on Income. This is evidenced by the tcount value for the Online/E-Commerce Transaction variable (4.514) which is greater than ttable (1.984) and a sig value of 0.000 <0.05, and Halal Labeling has a positive and significant effect on income. This is evidenced by the tcount value for the Halal Labeling variable (3.787) which is greater than ttable (1.984) and a sig value of 0.027 <0.05. And based on the F test Working Capital, Online/E-Commerce Transactions, and Halal Labeling have a simultaneous and significant positive effect on Revenue. This is evidenced by the Fcount value of (22.691) greater than Ftable (2.70) and a sig value of 0.000 <0.05. And from the results of testing the coefficient of determination shows that the value of R Square is 0.415. This shows that the independent variables, namely Working Capital, Online/E-Commerce Transactions, and Halal Labeling, are able to explain the dependent variable, namely Income of 41.5%, the remaining 58.5% is explained by other variables outside the regression model.